Conceptual Formulation of the Unẓur wa Qul Method in Islamic Religious Education in Modern Islamic Boarding Schools - Indah Rahma Sintia. AM; Asmi Indriani; Aldi Rahmat. AM (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This research is in the realm of Islamic Religious Education, specifically the development of learning methodology in modern Islamic boarding schools. Based on the need for an integrative and contextual approach, this article aims to conceptually formulate the Unẓur wa Qul method based on reflective observation and communicative articulation to integrate cognitive, affective, and psychomotor dimensions holistically. This research uses a qualitative approach through literature study. Data collection techniques are carried out by reviewing various classical and contemporary literature relevant to learning theory, Islamic epistemology, and Islamic boarding school educational practices. Data analysis is carried out descriptively analytical and conceptual synthesis, while data validity is tested through theoretical triangulation and comparison between literatures. The hypothesis of this research is that the Unẓur wa Qul method has a strong epistemological foundation in the Islamic scientific tradition and is relevant to be contextualized in Islamic Religious Education learning in modern Islamic boarding schools. The results of the study indicate that the Unẓur wa Qul method can be formulated as a learning model based on critical reflection and active communication that encourages students' dialogical participation. This research's contribution lies in enriching the methodology of Islamic Religious Education through systematic and applicable conceptual reconstruction. These findings emphasize the importance of integrating reflection and verbal expression in developing transformative learning in modern Islamic boarding schools.